The Parallel Market for Foreign Exchange in an Oil Exporting Economy : The Case of Iran, 1978-1990 - Mazarei, Adnan (IMF Working Papers; Working Paper ;, 1995)
This paper provides a model for the determination of the parallel market exchange rate premium in a country where oil export earnings accrue directly to the government, and foreign exchange is centrally allocated for the importation of specific goods. Next, it studies the parallel market for foreign exchange In the Islamic Republic of Iran during the period 1978-90. The paper then examines the various time series properties of parallel market exchange rate in Iran, and the evidence of the role of oil and non-oil exports in the determination of the parallel market premium.